Before the First Token: Benchmarking Data Preprocessing in Vision-Language Models - Zohdi, Sepideh; Wang, Lin (The 6th Workshop on Machine Learning and Systems (EuroMLSys))

Reinforcement Learning: A Comprehensive Open-Source Course - Abdelwanis, Ali Hassan Ali; Haucke-Korber, Barnabas; Jakobeit, Darius; Kirchgässner, Wilhelm; Meyer, Marvin; Schenke, Maximilian; Vater, Hendrik; Wallscheid, Oliver; Weber, Daniel (Journal of Open Source Education)

Spectral theory for transfer operators on compact quotients of Euclidean buildings - Hilgert, Joachim; Kahl, Daniel; Weich, Tobias (arXiv:2603.26949)
In this paper we generalize the geodesic flow on (finite) homogeneous graphs to a multiparameter flow on compact quotients of Euclidean buildings. Then we study the joint spectra of the associated transfer operators acting on suitable Lipschitz spaces. The main result says that outside an arbitrarily small neighborhood of zero in the set of spectral parameters the Taylor spectrum of the commuting family of transfer operators is contained in the joint point spectrum.

Using Attack and Failure Propagation Analysis for Context-Aware Security Control Suggestions - Trentinaglia, Roman; Koch, Thorsten; Bodden, Eric (Proceedings of the 14th International Conference on Model-Based Software and Systems Engineering)

Digital Fascism and Digital Capitalism - Fuchs, Christian (Philosophy & Social Criticism)

Aspects of Parameter Identification for a Micromorphic Continuum applied to a Cold‐Box Sand - Börger, Alexander; Mahnken, Rolf; Caylak, Ismail; Ostwald, Richard (Proceedings in Applied Mathematics and Mechanics)
ABSTRACT This work is concerned with the modeling of a cold‐box sand, a composition of sand grains and a resin binder. To this end, experiments are performed, which show the following characteristics: localization phenomena in the form of a shear band, softening behavior in the force‐displacement curve, and asymmetric behavior for compression and tension. To model this complex material behavior, a micromorphic continuum is used. In the present contribution, we focus on the linear‐elastic regime and demonstrate the identifiability of micromorphic material parameters under deliberately induced inhomogeneous deformation states. In addition to the degrees of freedom of a classical continuum, the micromorphic model has additional degrees of freedom, introduced here in a phenomenological sense to represent kinematically enriched deformation modes associated with the granular microstructure. Accordingly, the micromorphic fields are not interpreted as a separate physical scale (e.g., “binder” vs. “grains”), but as an effective continuum description at the specimen scale. This contribution addresses parameter identification for a micromorphic model of cold‐box sand, with a clear separation between homogeneous deformation states governing classical elastic parameters and inhomogeneous states required to activate and identify micromorphic length‐scale parameters. The main challenge lies in identifying the micro material parameters. To determine these, the corresponding gradient terms in the constitutive formulation must be triggered via properly tuned experiments. Micro‐parameter identification is demonstrated using synthetic data generated from a boundary‐value problem with inhomogeneous displacement fields. The chosen benchmark enables controlled activation of gradient terms and thereby renders optimization‐based identification of micromorphic parameters feasible. The synthetic example is deliberately chosen to assess feasibility and identifiability under controlled conditions, thereby isolating micromorphic identifiability aspects from experimental uncertainties. The novelty of the contribution lies in explicitly linking micromorphic parameter identifiability to kinematic inhomogeneity, and in demonstrating this link within a tractable forward– inverse setting for a linear‐elastic micromorphic continuum.

Is procrastination among students lower in group work? Evidence from a registered field experiment - Koppenborg, Markus; Hüffmeier, Joachim; Klingsieck, Katrin B. (British Journal of Educational Psychology)
Abstract Background Research on procrastination mostly focuses on person‐related antecedents and neglects situational and social factors, such as group work. Prior research indicates that conjunctive and additive group work may increase individual effort and performance as compared to individual work. Aims Based on these findings, we investigate whether conjunctive and additive group work may also help reduce procrastination as compared to individual work. Methods In a registered field experiment, N = 218 students with high levels of trait procrastination worked on an academic task over the course of 10 days in one of three conditions (individual work vs. conjunctive group work vs. additive group work). Dependent variables comprised task procrastination, task performance, and positive and negative task‐related affect. Results Regarding conjunctive group work, results are mixed, with some evidence that conjunctive group work leads to lower procrastination as compared to individual work. Both types of group work resulted in higher negative task‐related affect when assessed prospectively. No other effects were found. Conclusions The findings contribute to the idea that targeted changes in the learning environment, such as the implementation of group work, may help reduce procrastination.

Symbolic haunting: first-generation university students’ limited sense of entitlement - Lin-Januszewski, Liang-Wen (British Journal of Sociology of Education)

Investigation of Surface Roughness Effects on Flow Patterns and Thermal Performance in Additively Manufactured Channels - Hollenhorst, Viola; Riese, Julia; Kenig, Eugeny Y.

Keuchen, Marion/ Lindemeyer, Sabine: Demokratiebildung anhand eines (schul-)seelsorglichen Rituals im Rahmen der Lehramtsausbildung - Keuchen, Marion; Lindemeyer, Sabine (Seelsorge im Lebensraum Schule. Ökumenische Perspektiven)

Bridging Systems Theory and Information Systems: A Framework for Designing Complex Information Systems - Ibrahimli, Ulvi; Hemmrich, Simon; Winkelmann, Axel (Communication of the Association for Information Systems)
Information Systems (IS) is rooted in systems theory. Systems theory offers powerful concepts to address challenges of growing system complexity and non-systemic design approaches in information systems. Despite its systemic origins, systems theory remains a peripheral topic in IS. The study addresses this gap by introducing a comprehensive framework of 52 systems-theoretical concepts to guide the design of complex IS artifacts. We synthesize scattered systems knowledge from diverse disciplines to provide a unified level of abstraction for complex information system design. We apply the framework to a use case of business reputation systems to show how the systems lens informs the design of a novel, complex information system. We make three key contributions to the literature. First, the framework provides a common ground for interdisciplinary research in information system design. Second, it offers a unified level of abstraction grounded in systems theory that serves as a coherent basis for artifact design. Third, it demonstrates the potential of systems theory as a foundational justificatory knowledge base. Furthermore, we provide guidance on applying the framework across multiple modes of reasoning, alongside further application guidelines. The study thus serves as a bridge between the body of systems knowledge and contextual design in IS.
Keywords: Information Systems Research; Systems Theory; System Complexity; System Design; Design Science

A blockchain-based reputation system for consulting - Hemmrich, Simon; Nissen, Volker (Advanced Studies in Consulting Research and Digitalization – A Scientific Update on the Digital Transformation of the Consulting Industry. Springer.)
Trust between client and consultant is perhaps the most important asset in con-sulting, as this is a highly intangible knowledge-intensive business that concerns is-sues of outstanding strategic and operational importance for the customers. Cli-ents who have not worked with a particular consultancy face considerable risk when they place an order while lacking reliable information about the service quality they can expect. There is a strong link between trust and reputation, as the positive reputation of a consultancy can act as a substitute for a new client’s missing individual experience with the provider, fostering trust in the service quali-ty. Thus, creating, maintaining, and demonstrating a good reputation is of signifi-cant importance for consultancies in a very competitive industry. To facilitate trustworthy signals, we design and implement a novel reputation mechanism that carries a monetary weight stored on a blockchain network as an immutable, decentralized, and transparent ledger. Based on an implementation in the Ethereum network and subsequent evaluation, we conclude that the reputation mechanism can contribute to leveling information asymmetry and reducing risk while increasing reputation and trust. The mechanism lends itself to being used in other business-to-business scenarios that suffer from similar information asymmetries.
Keywords: Reputation Systems; Consulting; Design Science Invention; Incentive; Blockchain; Monetary ratings; building trust; reduce information asymmetry consulting; B2B reputation system; consulting risk reduction; supplier evaluation system

Reputation as a Sociotechnical Design Problem: A Social Systems Theory Lens for Business Reputation Systems - Ibrahimli, Ulvi; Hemmrich, Simon; Winkelmann, Axel

Fabrication of uniform, high-field-enhanced plasmonic satellite clusters using multidewetting - Kim, Minjun; Devaraj, Vasanthan; Seo, Hyeon-Seok; Eom, Seongjae; Lee, Jeong-Su; Lee, Donghan; Zentgraf, Thomas; Lee, Jong-Min; Jeon, Min Yong (Quantum Sensing and Nano Electronics and Photonics XXII)

Lehrkräfteprofessionalisierung im Sachunterricht – Chancen und Herausforderungen durch Künstliche Intelligenz (KI) - Becher, Andrea; Diederich, Julia; Gläser, Eva (Perspektiv(en)wechsel. Sachunterricht neu denken)

Viehhaltung - Droß-Krüpe, Kerstin; Ghetta, Marcello (RAC)

Counting Frobenius extensions over local function fields - Klüners, Jürgen; Müller, Raphael (arXiv:2604.02152)
We determine the asymptotic growth of extensions of local function fields of characteristic p counted by discriminant, where the Galois group is a subgroup of the affine group AGL_1(p). More general, we solve the corresponding counting problems for all groups which arise in a tower of a cyclic extension of order p over a cyclic extension of degree d coprime to p. This in particular give answers for certain non-abelian groups including S_3, dihedral groups of order 2p, and many Frobenius groups.

Rezension zu: Wewer, G.: Nach der Kritik: Reformen im Weltsport? - Meier, Heiko; Sennefelder, Lisa (Sport und Gesellschaft)

Deutsch als Garant für demokratische Teilhabe? Linguizismuskritische Anfragen an ein Verständnis von Demokratiebildung im Deutschunterricht - Büttner, Denise; Füllekruss, David (Demokratiebildung in Theorie und Praxis: Synergien zwischen Schulforschung und Deutschdidaktik)

Influence of deposition temperature and thickness of ALD-TiO2 on planar perovskite solar cell performance - Qudsia, Syeda; Weiss, Alexander; Sirkiä, Saara; Wang, Fuzeng; Rosqvist, Emil; Los Arcos, Teresa De; Weinberger, Christian; Halme, Janne; Kemell, Marianna; Smått, Jan-Henrik (Applied Surface Science)
In perovskite solar cells (PSCs), electron transport layers (ETLs) play an important role in the selection and transport of electrons. Understanding the properties of these layers in relation to device performance is essential for optimizing solar cell efficiency and enabling their integration into emerging architectures, such as flexible solar cells. Here, we deposited TiO2 at different thicknesses using atomic layer deposition (ALD), a technique well-suited for producing uniform and pinhole-free films. The crystal structure of the layers was controlled by depositing the films at three different temperatures: 150 °C, 250 °C, and 350 °C. The layers were characterized in detail to determine the morphology (by atomic force microscopy), surface composition (by X-ray photoelectron spectroscopy) and the crystal structure (by X-ray diffraction). The TiO2 layers were then incorporated as ETLs in planar perovskite solar cells to evaluate their influence on device performance. Higher deposition temperatures led to improvements in device fill factor and open-circuit voltage, leading to more efficient solar cells. Notably, the best device performance for the ALD-TiO2 layers was achieved with films deposited at 250 °C.
Keywords: Titanium dioxide; Atomic layer deposition; Electron transport layer; Perovskite solar cells